2020
DOI: 10.1109/access.2019.2960775
|View full text |Cite
|
Sign up to set email alerts
|

Data Augmentation for Deep Learning-Based Radio Modulation Classification

Abstract: Deep learning has recently been applied to automatically classify the modulation categories of received radio signals without manual experience. However, training deep learning models requires massive volume of data. An insufficient training data will cause serious overfitting problem and degrade the classification accuracy. To cope with small dataset, data augmentation has been widely used in image processing to expand the dataset and improve the robustness of deep learning models. However, in wireless commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 41 publications
(60 reference statements)
1
57
0
4
Order By: Relevance
“…Data augmentation techniques are considered as a proper solution for the drawbacks of insufficient training data. In [102], for example, a state-of-the-art LSTM-based AMR was presented to evaluate Gaussian noise, rotation, and flip methods of radio signals augmentation in both training and inference phases. Similarly in [103], RNN and LSTM were investigated for AMR.…”
Section: ) Rnn-based Methodsmentioning
confidence: 99%
“…Data augmentation techniques are considered as a proper solution for the drawbacks of insufficient training data. In [102], for example, a state-of-the-art LSTM-based AMR was presented to evaluate Gaussian noise, rotation, and flip methods of radio signals augmentation in both training and inference phases. Similarly in [103], RNN and LSTM were investigated for AMR.…”
Section: ) Rnn-based Methodsmentioning
confidence: 99%
“…Compared to random cropping, random erasing does not impact data integrity. In the field of AMC, Weijian Pan et al [12] effectively expanded training data by rotating constellation diagram and adding noise to it. Shiyao Chen et al [13] used generative adversarial network (GAN) [14] for data augmentation.…”
Section: ) Data Augmentation Methodsmentioning
confidence: 99%
“…The first part is signal embedding module. The data format in RML2016.10a is 2 × 128 , which can be directly used as input to LSTM, so the existing work such as [7], [12], [13] is to input IQ data directly into LSTM for processing. If a set of data is viewed as a sentence, then for the LSTM, the sentence is made up of 128 words, each of which is a vector of length 2.…”
Section: Single-layer Lstm Model Based On Attention Mechanismmentioning
confidence: 99%
“…Huang et al applied a few data augmentation methods, such as rotation, flip, and Gaussian noise, on the RadioML Dataset. Their experiments showed that the rotation method yielded the best accuracy [32], and needed fewer data to achieve relatively good results. For the convenience of application, exploring lightweight networks is also very important for AMC problems.…”
Section: B Deep Neural Network Methodsmentioning
confidence: 99%